2020
DOI: 10.1111/1467-9566.13223
|View full text |Cite
|
Sign up to set email alerts
|

A delicate balance between control and flexibility: Experiences of care and support among pre‐teenage children with type 1 diabetes and their families

Abstract: For children with type 1 diabetes, the period of adolescence is associated with higher blood glucose levels and increased psychological distress compared to other age groups. Focusing on pre-teens (9-12 years) with type 1 diabetes and their families has been suggested as key to understanding and reducing these challenges. The aim of this study was to explore: 1, how diabetes affects family life, 2, experiences of and needs for support and 3, how care responsibilities are negotiated among pre-teens with type 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
1
10
0
1
Order By: Relevance
“…The findings of this review also show that the experience of parents–in particular mothers–have some parallels with the experience of well siblings. Like the findings of this review suggest in relation to siblings, past research indicates that mothers also feel a need to protect their ill children from risks and dangers (Clark & Dumas, 2020; Pitchforth et al., 2011), which lead them to engage in a state of constant vigilance (Pals et al., 2021; Rifshana et al., 2017). In a similar way to what has been described by Webster (2018) in relation to sibling caring roles and responsibilities, past research also found out that mothers end up fulfilling the role of an alert assistant for their chronically ill child (Williams, 2000a).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The findings of this review also show that the experience of parents–in particular mothers–have some parallels with the experience of well siblings. Like the findings of this review suggest in relation to siblings, past research indicates that mothers also feel a need to protect their ill children from risks and dangers (Clark & Dumas, 2020; Pitchforth et al., 2011), which lead them to engage in a state of constant vigilance (Pals et al., 2021; Rifshana et al., 2017). In a similar way to what has been described by Webster (2018) in relation to sibling caring roles and responsibilities, past research also found out that mothers end up fulfilling the role of an alert assistant for their chronically ill child (Williams, 2000a).…”
Section: Discussionmentioning
confidence: 62%
“…The onset of a chronic illness may lead siblings to experience a loss of sense of self within the family, as well as a loss of their family way of life (Woodgate, 2006a). Although there has been a shift from hospital to the home recently (Fortier et al., 2011), few studies have explored the everyday experiences of families when a child suffers from a chronic illness within the home setting from a sociological point of view (Pals et al., 2021). Caring has been found to be a central defining feature of sibling relationships and interactions (Edwards et al., 2005; Gillies & Lucey, 2007) and a common—albeit usually a hidden—experience within contemporary western families (Kosonen, 1996; Morrow, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Across all workshops, the same tools were used to facilitate dialogue among adolescents with T1D [22,24,25]. Author DG participated in all workshops, confirming that participants were presented with the same topics.…”
Section: Methodsmentioning
confidence: 85%
“…Following our good experiences with The Family Mirror, modified versions have been successfully used in workshops with other target populations, including children and adolescents with T1D [24,25]. The overall idea and design of the tool were retained, but several statements and pictograms concerning, e.g., partners and offspring were left out because they were not relevant to the daily life of children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…When the child is young, this responsibility for diabetes management belongs solely to the parents, but as the child grows, the responsibility will gradually shift from the parent to the child. Hence, it is vital to consult and involve the parents, as their commitment and support are prerequisites for the well-being of the child [ 11 , 12 ]. Having to deal with illness management tasks in everyday life places a heavy burden on the children and their parents.…”
Section: Introductionmentioning
confidence: 99%